The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.2307/3870024
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Attenuation by a Normally Virulent Satellite RNA of Turnip Crinkle Virus Is Associated with the Coat Protein Open Reading Frame

Abstract: Many satellite RNAs (sat-RNAs) can attenuate or intensify the symptoms produced by their helper virus. Sat-RNA C, associated with turnip crinkle virus (TCV), was previously found to intensify the symptoms of TCV on all plants in which TCV produced visible symptoms. However, when the coat protein open reading frame (ORF) of TCV was precisely exchanged with that of cardamine chlorotic fleck virus, sat-RNA C attenuated the moderate symptoms of the chimeric virus when Arabidopsis plants were coinoculated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Although the primary function of CP is structural, several studies have shown that it also has a vital role in virus-host interactions. This is supported from studies showing that certain TCV CP mutants cause altered symptom phenotypes (25) and that CP is responsible for modifying symptoms caused by satellite RNAs (31,32). In addition, it is well established that TCV CP is needed for systemic movement in most hosts, and cell-to-cell movement in Nicotiana benthamiana (20,34).…”
supporting
confidence: 51%
“…Although the primary function of CP is structural, several studies have shown that it also has a vital role in virus-host interactions. This is supported from studies showing that certain TCV CP mutants cause altered symptom phenotypes (25) and that CP is responsible for modifying symptoms caused by satellite RNAs (31,32). In addition, it is well established that TCV CP is needed for systemic movement in most hosts, and cell-to-cell movement in Nicotiana benthamiana (20,34).…”
supporting
confidence: 51%
“…It was suggested that the highly structured nature of these subviral RNAs limited access by the RISC complex and this difference of accessibility accounted for preferential accumulation of the more highly structured smaller RNAs. In this context, the identification of suppressor activity associated with TCV CP provides a possible explanation for the observed role of the CP in modulating the effects of sat-RNA C on symptom development and satellite RNA accumulation [46].…”
Section: Some Common Features Of Virus-encoded Silencing Suppressorsmentioning
confidence: 99%
“…satC, by interfering with the replication of TCV in protoplasts (16) and accumulation in plants (20), was thought to fit that general description. However, the ability of satC to enhance the symptoms of TCV only in plants that display visible symptoms when infected with TCV alone suggested that the satRNA enhances the ability of the virus to colonize the plant and interact with cellular factors (20,54).…”
mentioning
confidence: 99%